Mutation of POC1B in a Severe Syndromic Retinal Ciliopathy - Beck, Bodo B.; Phillips, Jennifer B.; Bartram, Malte P.; Wegner, Jeremy; Thoenes, Michaela; Pannes, Andrea; Sampson, Josephina; Heller, Raoul; Göbel, Heike; Koerber, Friederike; Neugebauer, Antje; Hedergott, Andrea; et al. (Human mutation, 2014)
ABSTRACT We describe a consanguineous Iraqi family with Leber congenital amaurosis (LCA), Joubert syndrome (JBTS), and polycystic kidney disease (PKD). Targeted next‐generation sequencing for excluding mutations in known LCA and JBTS genes, homozygosity mapping, and whole‐exome sequencing identified a homozygous missense variant, c.317G>C (p.Arg106Pro), in POC1B, a gene essential for ciliogenesis, basal body, and centrosome integrity. In silico modeling suggested a requirement of p.Arg106 for the formation of the third WD40 repeat and a protein interaction interface. In human and mouse retina, POC1B localized to the basal body and centriole adjacent to the connecting cilium of photoreceptors and in synapses of the outer plexiform layer. Knockdown of Poc1b in zebrafish caused cystic kidneys and retinal degeneration with shortened and reduced photoreceptor connecting cilia, compatible with the human syndromic ciliopathy. A recent study describes homozygosity for p.Arg106ProPOC1B in a family with nonsyndromic cone‐rod dystrophy. The phenotype associated with homozygous p.Arg106ProPOC1B may thus be highly variable, analogous to homozygous p.Leu710Ser in WDR19 causing either isolated retinitis pigmentosa or Jeune syndrome. Our study indicates that POC1B is required for retinal integrity, and we propose POC1B mutations as a probable cause for JBTS with severe PKD. We describe a family with severe congenital retinal degeneration (LCA), Joubert syndrome and massively enlarged polycystic kidneys. It results from a homozygous missense mutation in POC1B, a gene essential for ciliogenesis, basal body and centrosome integrity. Knockdown in zebrafish evokes a corresponding ocular‐renal phenotype. In view of simultaneous studies reporting mutations in non‐syndromic cone‐rod dystrophy, our findings suggest that POC1B mutations may cause retinal ciliopathies of variable severity.